Efficient Trading Strategies in the Presence of Market Frictions - Jouini, Elyès; Kallal, Hédi (Review of Financial Studies, 2001)
In this paper we provide a price characterization of efficient consumption bundles in multiperiod economies with market frictions. Efficient consumption bundles are those that are chosen by at least one rational agent with monotonic state-independent and risk-averse preferences and a given future endowment. Frictions include dynamic market incompleteness, proportional transaction costs, short selling costs, borrowing costs, taxes, and others. We characterize the inefficiency cost of a trading strategy -the difference between the investment it requires and the largest amount required by any rational agent to obtain the same utility level - and we propose a measure of portfolio performance based on it. We also show that the arbitrage bounds on a contingent claim to consumption cannot be tightened based on efficiency arguments without restricting preferences or endowments. We examine the efficiency of common investment strategies in economies with borrowing costs due to asymmetric information, short selling costs, or bid-ask spreads. We find that market frictions generally change and typically shrink the set of efficient investment strategies, shifting investors away from well-diversified strategies into low cost ones, and for large frictions into no trading at all. Hence we observe strategies that become inefficient with market frictions, as well as strategies that are rationalized by market frictions.